Effectiveness of Pessoa’s universal technique for single marking in mastoplasty performed while training plastic surgeons - Salustiano Gomes de Pinho Pessoa; Aleksandra Markovic; José Alberto Dias Leite (Revista Brasileira de Cirurgia Plástica)
Introduction: Reduction mastoplasty is still a challenging procedure for plastic surgeons. The Objective is to show the results of the treatment of different degrees of breast hypertrophy using Pessoa's single marking technique performed while training plastic surgeons. Methods: A retrospective cohort of 95 patients underwent reduction mastoplasty using Pessoa's technique. The cohort included patients with breast ptosis, hypertrophy, gigantomastia, and/ or breast asymmetry. The procedures were performed by first-, second-, and third-year residents. The exclusion criteria were psychological disorders, morbid obesity, and/or indication for prosthesis implantation without skin and/or areola reduction. The analyzed factors were age, sex, final size, patient's degree of satisfaction, complications, and difficulties experienced by the residents in performing the surgery. Results: All patients were women aged between 21 and 61 years. Of the patients, 90.53% reported being very satisfied; 5.26%, satisfied; 3.16%, poorly satisfied; and 1.05%, dissatisfied. The complications observed were necrosis of the nipple-areola complex (1.05%), epidermolysis (11.58%), and suture dehiscence (9.47%). The rate of difficulty experienced by the residents varied between 11.1% and 55.6%, depending on the step of the surgical procedure. Conclusions: A high degree of satisfaction was reported by both the patients and residents. The results confirm the effectiveness of the technique while training residents.